Les pays émergents à la conquête des marchés mondiaux - Marie Coris; Alain Rallet (Revue de la Régulation)
In Europe and the United States, the attractiveness of emerging countries is often reduced to the debate on the transfer of economic activities towards these countries. This debate underestimates the opposite phenomenon, namely the penetration of the markets in developed countries by global firms stemming from emerging countries. Here is discussed the example of the software industry which has experienced a dramatic growth in India as in China for 15 years. Now, the sector-based trajectories of these two countries lead to differentiated but very real processes of contesting the markets of developed countries by global firms of emerging countries.